Reading aloud in Lewisham: an exploration of adult reading‐aloud practices. (22nd December 2014) - Duncan, Sam
Abstract: This paper analyses initial findings of a qualitative pilot study of the reading‐aloud practices of 17 adults in the London Borough of Lewisham. Although the dominant contemporary image of reading is that of a silent activity and within literacy provision it is frequently assumed that reading aloud is not a 'natural' 'real life' adult practice, anecdote suggests that adults do indeed read aloud, but these practices are overwhelmingly undocumented. This study is the first stage in developing a better understanding of contemporary adult reading‐aloud practices. Semi‐structured interviews were used to ask adults whether, what, where, how and why they read aloud. Initial findings reveal the ubiquitous nature of reading aloud in adult life, across a range of life domains (spiritual life, family life, work and learning) and for different self‐selected purposes (to memorise, to understand, to write and for fellowship). Initial findings reinforce the importance of expanding our definitions and conceptualisations of reading to recognise the diversity and changing nature of real life practices, and suggest implications for our understanding of the role of reading in adult life, for literacy education and for future research.